MEMBANGUN KESEFAHAMAN INDONESIA-MALAYSIA MELALUI KOMUNIKASI ANTARBUDAYA - Junaidi, Junaidi (Jurnal Ilmu Budaya, 2008)
This writing aims to describe basic principle of intercultural communication and relates it with intercultural communicative process applied by Indonesian and Malaysian communities. This writing concludes that the application of intercultural communication needs to be conducted in Indonesia and Malaysia relation since the different relation of nations needs certain strategies to behave to keep mutual comprehensions between the two nations. The appliction of the intercultural communication contributes positives impacts on establishing mutual comprehensions between Indonesia and Malaysia.